KARTINI: SANG PENYIBAK FAJAR NASIONALISME INDONESIA - Yuliati, Dewi (Sabda: Jurnal Kajian Kebudayaan, 2017)
This aticle presents the discussion on Kartini as an Indonesian nationalist heroine who is still becoming public debate. It is very important to trace the historical records of Kartiniâ€™s activities in connection with her dreams to promote the life quality of her nation. It can be stated that Kartini has an important role to open the first gate for the rising Indonesian consciousness through her competence as a cultural diplomat by proposing her letters which were sent to her friends in the Netherlands. Finally, her dream came true when â€œKartini Schoolsâ€ were opened in Semarang, Bogor, Batavia, and Madiun in 1913-1914, and her ideas became the inspiring ideology of the Indonesian nationalism movements which arose after Kartini died on 17th September 1904.